The role of leadership in promoting innovation within small and medium enterprises: A study on how different leadership styles affect innovation rates in small and medium enterprises (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study examined the role of leadership in fostering innovation within small and medium-sized enterprises (SMEs), focusing on the importance of effective leadership in driving creativity and improving organizational performance. Leaders in SMEs face various challenges related to limited resources and competitiveness in rapidly changing markets. This study analyzes the impact of different leadership styles, such as transformational and motivational leadership, on innovation development in these enterprises. These results were analyzed, and they relied heavily on leadership to encourage contribution, at a rate of 48%, and appeared creative in innovation, as 44.9% of the participants in the questionnaire were, and they only participated in an integral part of the institutions’ culture, and some participants also participated in being involved significant support was not completed, as 34.7% was not completed. The findings reveal that leaders who adopt inspirational leadership styles and encourage creative thinking contribute directly to enhancing innovation levels and increasing the organization's competitiveness. The study offered recommendations to enable leaders to foster an innovative environment by promoting open communication, supporting new experiments, and investing in skill development descriptive principle of Newton's analysis, the questionnaire tool, was used, and the data was analyzed using the Excel program, and several results were reached, the most prominent of which are: that institutions rely heavily on leadership for encouragement, that practicing commerce is important in supporting creative and innovative employees, and that leadership is a small commercial institution. She works largely in the field of health care, and ended up studying after being among the top achievers: Promoting a creative work environment, encouraging effective communication, encouraging cooperation between different teams.
Keywords: Leadership; Innovation; Small and Medium Enterprises (SMEs); Transformational Leadership; Competitiveness